BEHAVIORAL BASED LEARNING - Kandiri Kandiri (LP2M Universitas Ibrahimy, 2017)
Behavior-based learning is inspire by some of behavioral figures led by Ivan Povlov, Thorndike, skinner and John B Watson are two foundations: 1) There are good behaviors (adaptive) and some mal-adaptive ones that can both be learned , 2) if the behavior can be learned, then it will followÂ principle of learning is change of behavior. In short, if learning behavior is good or pleasant, it tends to be reinforced and repeated, but if learning behavior is bad, it tends to be rejected, it will not be reinforced and repeated._x000D_ Teachers-parents in the past few decades have applied the principles of behavioral learning theory in teaching and educating children's discipline, children who have good grades in a subject area or a good ranking in their class are given more attention by their parents. Many learning theories agree that no matter what As well as the level / grade and achievement that child or learner achieves, students learn from teachers, peers, learning resources in book, and classroom layout. What students learn can be measured as specific knowledge, even they learn something more complex such as attitudes, community behavior, emotions, and reactions of others, and one of the most important teacher jobs is how to formulate complex situations such as learning principles And motivation can be understood._x000D_ Behavioristic theory is perfect for the acquisition of skills that require practice and habituation that contain elements such as: speed, spontaneity, flexibility, reflexes, endurance and so forth, this is evidenced by the opinion of behavioral experts, such as: 1. Ivan Petrovic Pavlov With the theory: Theory of Connectionism or bond psychology, Theory of Classical Conditioning (conditional reflexes). 2. Edward Lee Thorndike with the theory: Law of readiness, Law of exercise, Reaction reaction law (Multiple Response), 3. Skinner with Theory of Operating Conditioning (Burrhus Frederic Skinner, 4) John B. Watson theory with theory: Theory is called SARBON stands for S (stimulus) + R (response) + Bond (d), states that behavior is complex and can be analyzed into unity of stimulus and response called reflex . Learning is process of occurrence of reflex / conditional response through stimulus changed. His opinion, that humans are born with some reflexes and emotional reactions of fear, love, anger and others and all his behavior